Maternal Knowledge of Antenatal Care, Teratogens and Patient Satisfaction in Tertiary Care Hospitals of Rawalpindi /Islamabad: a Cross-Sectional Analytical Study - Mishal Suhail; Awan, Bushra Ameer Saeed; Shamim, Amna; Zeb, Uswa (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess maternal knowledge of antenatal care teratogens and to determine patient satisfaction among women visiting tertiary care hospitals of Rawalpindi/Islamabad.Study Design: Cross-sectional analytical study.Place and Duration of Study: Two Tertiary Care Hospitals of Rawalpindi/ Islamabad, Pakistan from Jan to May 2023.Methodology: The study was conducted on pregnant females visiting tertiary care hospitals in Rawalpindi and Islamabad from January to May 2023. Participants aged 18-45 were recruited through a convenience sampling technique. A pre-tested questionnaire comprising socio-demographic and Likert scale scoring regarding knowledge of antenatal care teratogenic medicine and consultation satisfaction was used. Differences in scores by age, perinatal status, education, and income were analysed.Results: The study included 120 participants, of which 86(71.7%) were less than 30 years of age, 34(28.3%) were more than 30 years, and 47(39.5%) of the women had attended school till matriculation. The median knowledge of antenatal care score was 69.3(79.6-58.7), teratogen score was 85.1(95.3-74.5) and patient satisfaction score was 73.4(79.7-66.3). The patient’s status (p